Hubungan Motivasi dan Beban Kerja dengan Kinerja Perawat di Instalasi Rawat Inap RSUD Kota Makassar - Suci Fajriani S; Muhammad Alwy Arifin; Suci Rahmadani (Yayasan Literasi Sains Indonesia, 2022)
Nurses are the implementing elements of service activities of a hospital so that the quality of nurses will determine hospital performance. Therefore, nurses who have good performance are needed. Nurse performance is closely related to how much motivation and workload nurses have in providing health services to patients. Meanwhile, the number of nurses at the Makassar City Hospital is still inadequate, causing the nurses' workload to be quite high. However, in carrying out nursing care, nurses have their own motivations that encourage them to carry out their duties and responsibilities as well as possible. This study aims to determine the relationship between motivation and workload with the performance of nurses in the inpatient installation of Makassar City Hospital. The type of research used is quantitative research using a cross sectional study approach. The population in this study were all nurses who served in the inpatient installation of the Makassar City Hospital. Determination of the sample by the method of total sampling with a total sample of 69 nurses. The results of the study using chi-square showed that motivation (p=0.000) and workload (p=0.044). The p value of all independent variables <0.05 so that there is a relationship between motivation and workload with the performance of nurses in the inpatient installation of Makassar City Hospital.